ISOLATION OF BACTERIA AND FUNGI IN TISSUES OF PAICHE (ARAPAIMA GIGAS) REARED IN CAPTIVITY - Serrano M., Enrique (2014)
This study evaluated the presence of bacterial and micotic agents in 120 paiches(Arapaima gigas) in two fish farms in the Peruvian Amazon. Findings included sevenbacterial agents: Pseudomonas spp, Bacillus spp, Staphylococcus spp, Streptococcusspp, Escherichia spp, Aeromonas hydrophila and Corynebacterium spp, and one fungus:Saprolegnia spp.